Effects of nonspecific endurance training on specific performance in inline speedskating - Hildebrand, C.; Abel, T.; Hesse, C.; Claßen, S.; Strüder, H. K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: To be competitive and successful, inline speedskaters require a mix of swiftness and power combined with a high aerobic and anaerobic capacity. Thus, a highly developed aerobic performance level enables the athletes to sustain a high average of speed (40 km/h), as well as ensuring a fast recovery between the tactically high intensive efforts of attacks (Thomas et al. 2004). Since the right period to develop this ability is in winter, a sport-specific training is weather-related not possible. Hence, we investigated the influence of a nonspecific training (cycling, running) on inline speedskaters` sport specific endurance performance. Methods: 14 high level inline speedskaters (7 male, 7 female, 24 ± 8 years, 175.4 ± 9.7, 67.5 ± 11.2 kg, body fat: 15.3 ± 2.2 %) were randomized divided in two groups (running, cycling) and trained at 60% of VO2max over 7 weeks with 2 sessions per week (81-90 min) each on treadmill or cycle ergometer respectively. Before and after the training intervention all subjects performed an incremental exhaustive specific and nonspecific (cycling or running) test. In addition to blood lactate (LA) and glucose (BGL) concentration (mmol/l), oxygen uptake (VO2, absolute [l/min] and relative [ml/kg/min]), ventilation (VE [l/min]), ventilatory equivalent (VE/VO2 [l/min]) respiratory quotient (RQ) and heart rate (HR [b/min]) were measured or calculated through a portable spirometry system to determine the exercise effects. Results: Body fat was reduced significantly in both groups (cycling: p=0.021, running: p=0.004). On sub-maximal efforts all measured parameters were significantly (p.0.02) improved from pre to post without any group effect. Similar results occurred in maximum values for VO2, RQ and VE/VO2 (p=0.01) at the same exercise intensity. The cycle exercise resulted in significant decreases in maximum HR (p=0.021) and BGL (p=0.004) during inline speedskating. The corresponding effect sizes are d=0.95 and r=0.72 respectively. Conclusion: The results indicate that nonspecific training at 60% of VO2max effects inline speedskaters` endurance performance positively. Although most of the analyzed parameters did not differ significantly after the different types of training, the cycling-specific effect on maximum HR and BGL should be considered for optimal fundamental endurance training. These results coincide with the assumption that cycling imitates superiorly the inline speedskating movement pattern than running (Martinez et al. 1993).